Dissection of genetic factors underlying rust resistance of a widely-grown bread wheat (Triticum aestivum) cultivar ‘PBW343’ - DATTA, D; PRASHAR, M; BHARDWAJ, S C (The Indian Journal of Agricultural Sciences, 2011)
Genetic basis of rust resistance was investigated in a bread wheat (Triticum aestivum L. emend. Fiori and Paol) cultivar ‘PBW343’ which is grown in more than 8 million ha in north-western plains zone and adjoining areas of India. The study showed that ‘PBW343’ is resistant to leaf rust pathotypes except those virulent on Lr26. Single dominant gene imparted resistance against pathotype ‘109R31-1’. ‘PBW343’ was resistant to all stem rust pathotypes including those virulent on Sr24. At least 2 stem rust resistance genes were detected in ‘PBW343’. Single dominant gene was responsible for resistance to stem rust pathotype ‘62 G29’ and 2 independent dominant genes imparted resistance against pathotype ‘75 G5’. ‘PBW343’ was resistant to stripe rust pathotypes except a new race ‘78S84’. Two seedling resistance genes governed resistance against stripe rust in ‘PBW343’. New pathotypes virulent on ‘PBW343’, identified in India (leaf and stripe rusts) or Central Asia (stripe rust) or Uganda (stem rust), are potentially capable of incurring economic loss to this cultivar which may adversely affect wheat production in India